Achieving an ultralow emission of nitrogen oxides by using activated carbon with hydrophobic modification. (15th September 2021) - Fang, Zhongqiu; Tao, Jiabo; Yu, Xinhai; Zhao, Shuangliang; Li, Hailong; Tu, Shan-Tung
Abstract: Selective noncatalytic reduction (SNCR) systems have been widely used for denitrification in small capacity boilers, such as biomass- and waste-fueled boilers. However, these systems cannot meet the requirements of ultralow emission regulations, i.e., 50 mg m −3 . This work proposes a new solution that combines SNCR and activated carbon (AC). To solve the problem caused by the wettability of AC, which can significantly reduce the quantity of NO x that can be adsorbed and block active cites, hydrophobic modification was employed to amend the properties of AC. The influences of the key operating parameters on the denitrification of AC, including the reaction temperature, O2 concentration, feed gas flow rate, and contents of SO2 and CO2, have been investigated experimentally. A novel solution that combines AC and SNCR was proposed for industrial applications, and the economic feasibility has been verified. The results have demonstrated that this hybrid solution can achieve a low levelized cost of denitrification, which is 59.8% and 33.7% lower than those of SCR and hybrid SNCR/SCR. Graphical abstract: Image 1 Highlights: Hydrophobic modification alleviates wettability for denitrification using AC. Regeneration of AC ensure a high-efficiency and long-term denitrification. Levelized cost of SNCR + AC is superior to those of SCR and SNCR + SCR. NO x removal efficiency on AC was promoted by 26.1% in 97% RH after FAS grafting.